First Central Mediterranean Scientific Field Study on Recreational Fishing Targeting the Ecosystem Approach to Sustainability - Agius Darmanin, Sandra; Vella, Adriana (Frontiers in Marine Science, 2019)
The Maltese Islands have a very active recreational fishing community which may affect the coastal marine ecosystem. Despite this, studies to scientifically document the effects of this activity have been lacking prior to works between July 2012 and June 2017 presented here as a case study. This project, with the aim of collecting long-term data on the characteristics, trends, catches and impacts to fish populations of the recreational shore sport fishery at the national level also involved a pilot study on hobby shore angling. 2589 roving-access creel surveys conducted during 132 sport fishing events and 159 catches from hobby fishers were documented with the methodology used also applicable to shore fishing taking place in the Mediterranean and elsewhere. 90 species belonging to 29 families were documented with the most common being the Sparidae and Labridae. Catch per unit effort was higher for sport fishers with hobby fishers targeting larger fish. Results from this case study go to augment the limited and necessary knowledge on this fishing sector in the Mediterranean. Findings also indicate that recreational fisheries need to be taken into account when considering conservation measures for national, regional and global fisheries management.